2004
DOI: 10.1007/s00122-004-1593-0
|View full text |Cite
|
Sign up to set email alerts
|

Creation of BAC genomic resources for cocoa (Theobroma cacao L.) for physical mapping of RGA containing BAC clones

Abstract: We have constructed and validated the first cocoa ( Theobroma cacao L.) BAC library, with the aim of developing molecular resources to study the structure and evolution of the genome of this perennial crop. This library contains 36,864 clones with an average insert size of 120 kb, representing approximately ten haploid genome equivalents. It was constructed from the genotype Scavina-6 (Sca-6), a Forastero clone highly resistant to cocoa pathogens and a parent of existing mapping populations. Validation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The identification of QTLs for the aforementioned characters would facilitate the development of superior genotypes for planting and evaluation under specific environmental conditions. Guiltinan (2007) and Clement et al (2004) described the value of the recently constructed cacao bacterial artificial chromosome (BAC) libraries for gene discovery in cacao. Marcano et al (2009) reported on a genome-wide mapping study for yield factors and morphological traits in cacao.…”
Section: Molecular Approaches: Application Of Genomic Tools Gene Dismentioning
confidence: 99%
“…The identification of QTLs for the aforementioned characters would facilitate the development of superior genotypes for planting and evaluation under specific environmental conditions. Guiltinan (2007) and Clement et al (2004) described the value of the recently constructed cacao bacterial artificial chromosome (BAC) libraries for gene discovery in cacao. Marcano et al (2009) reported on a genome-wide mapping study for yield factors and morphological traits in cacao.…”
Section: Molecular Approaches: Application Of Genomic Tools Gene Dismentioning
confidence: 99%
“…Interestingly, such R‐loci often exist as clusters of resistance genes (Michelmore and Meyers 1998) as demonstrated by genetic and physical mapping and fluorescence in situ hybridization (Shen et al. 1998, Clement et al. 2004).…”
mentioning
confidence: 99%
“…Based on their sequence and structural conservation, cloning and genetic mapping of resistance gene analogues (RGAs) and PRs from different genomes with putative function in pathogen response are possible by using a degenerate primer approach (Leister et al 1996, Pflieger et al 2001. Interestingly, such R-loci often exist as clusters of resistance genes as demonstrated by genetic and physical mapping and fluorescence in situ hybridization (Shen et al 1998, Clement et al 2004. In beet, a number of RGAs have been identified either from expressed sequence tag (EST) databases or by PCR (Tian et al 2004).…”
mentioning
confidence: 99%
“…This QTL explained up to 51% of the phenotypic variance for resistance, while a secondary minor QTL was detected on chromosome 1, near a resistance gene analogue locus (Brown et al ., 2005; Faleiro et al ., 2006). A BAC library from ‘Scavina 6’ was constructed (Clement et al ., 2004) for map‐based cloning of this major gene. The major QTL was also reported in another mapping progeny derived from ‘SCA‐6 × ICS‐1’, which explained 35% of the phenotypic resistance to WBD (Queiroz et al ., 2003).…”
Section: Disease Controlmentioning
confidence: 99%